Animal : [large type] a novel - Taddeo, Lisa (Thorndike Press large print core, 2021)
"Joan has spent a lifetime enduring the cruelties of men. But when one of them commits a shocking act of violence in front of her, she flees New York City in search of Alice, the only person alive who can help her make sense of her past. In the sweltering hills above Los Angeles, Joan unravels the horrific event she witnessed as a child--that has haunted her every waking moment--while forging the power to finally strike back. Animal is a depiction of female rage at its rawest, and a visceral exploration of the fallout from a male-dominated society"--